2019
DOI: 10.1038/s41598-019-50397-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Mono-disperse Carbon Quantum Dots from Fennel Seeds: Photoluminescence analysis using Machine Learning

Abstract: Herein, we present the synthesis of mono-dispersed C-QDs via single-step thermal decomposition process using the fennel seeds (Foeniculum vulgare). As synthesized C-QDs have excellent colloidal, photo-stability, environmental stability (pH) and do not require any additional surface passivation step to improve the fluorescence. The C-QDs show excellent PL activity and excitation-independent emission. Synthesis of excitation-independent C-QDs, to the best of our knowledge, using natural carbon source via pyrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(170 citation statements)
references
References 51 publications
(116 reference statements)
10
151
0
Order By: Relevance
“…The bands at 1,700 and 1,600 cm −1 were attributed to the vibrational absorption bands of −COOH and C=C, respectively. All FTIR peak assignments agree well with those previously reported studies for CQDs prepared differently (Vinci et al, 2015 ; Zhang et al, 2017 ; Dager et al, 2019 ). No obvious functional group differences between CQDs are demonstrated in Figure 2 , which suggests synthesis mechanism is similar, if not the same, between all samples.…”
Section: Resultssupporting
confidence: 90%
“…The bands at 1,700 and 1,600 cm −1 were attributed to the vibrational absorption bands of −COOH and C=C, respectively. All FTIR peak assignments agree well with those previously reported studies for CQDs prepared differently (Vinci et al, 2015 ; Zhang et al, 2017 ; Dager et al, 2019 ). No obvious functional group differences between CQDs are demonstrated in Figure 2 , which suggests synthesis mechanism is similar, if not the same, between all samples.…”
Section: Resultssupporting
confidence: 90%
“…Thus C-QDs often have an amorphous structure and poor photostability. Recently, our group reported the synthesis of excitation independent C-QDs; however, the synthesis process was time and energy-consuming 18 . Despite recent advancements in the synthesis technologies, developing a cost-effective, nonetheless rapid, and energy-efficient process remains a challenge to synthesize graphitized-C-QDs.…”
mentioning
confidence: 99%
“…Synthesis of mono-dispersed carbon quantum dots via a single-step thermal decomposition method was reported using the fennel seeds (Foeniculum vulgare) ( Fig. 3) (Dager et al 2019); the prepared quantum dots showed significant colloidal, photostability, environmental stability (pH), and did not need extra surface passivation step for improving their fluorescence. Additionally, these particles demonstrated remarkable photoluminescence activity and excitation-independent emission.…”
Section: Eco-friendly and Sustainable Synthesis Of Carbon Quantum Dotsmentioning
confidence: 99%
“…Additionally, these particles demonstrated remarkable photoluminescence activity and excitation-independent emission. The effect of some factors like reaction time and temperature on pyrolysis provided insight into the formation of carbon quantum dots; these quantum dots can be applied in biosensing, cellular imaging, lightemitting diode, solar cell, supercapacitor, printing, and sensors (Dager et al 2019).…”
Section: Eco-friendly and Sustainable Synthesis Of Carbon Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation